PENDIDIKAN KESEHATAN INFEKSI VISUAL ASAM ASETAT DI KAMPUNGMELAYU KELURAHAN BATU BESAR KECAMATAN NONGSA - Septi Maisyaroh Ulina Panggabean; Fitri Sejati; Siti Nuraisah (LPPM Universitas Awal Bros, 2020)
Cervical and breast cancer are the cancer with the highest prevalence in Indonesia in 2013. The prevalence of cervical cancer is 0.8%. In the Riau Islands Province. North Maluku Province, and DI.Yogyakarta Province have the highest prevalence of cervical cancer at 1.5% based on the most estimated number of cervical cancer sufferers found in East Java and Central Java Provinces. One of the factors causing the high incidence of cervical cancer in women due to the low coverage of early detection due to lack of information on the public. Early detection of cervical cancer is an innovative breakthrough in health to reduce mortality and morbidity due to the cancer. The participants of this baby massage training health education are women of childbearing age with a range of ages 20 to 45 years of age and residing in the Malay kampong of Batu Besar sub- district, Nongsa District. Evaluation of increasing knowledge is done by pre and post test. The results showed that there was good knowledge of 85.3%, and participants who were willing to carry out IVA examinations were 72.4%. Conclusion of community service in the form of this training increased the knowledge and willingness of mothers to carry out IVA tests to reduce the number of cervical cancer, especially in the city of Batam